'Hardly gear for woman to meddle with': Kriemhild's Violence in Nineteenth-Century Women's Versions of the Nibelungenlied. (July 2021) - Boyle, Mary
Abstract : This article examines the depiction of violence in early female-authored translations and adaptations of the Nibelungenlied . For sixty years, anglophone reception of this text, then frequently characterized as the German national epic, was the preserve of male writers, but in 1877, Auber Forestier published Echoes from Mist-Land, a free adaptation. By 1905 she had been followed by four other women. Margaret Armour and Alice Horton produced fairly close translations. Two others, Lydia Hands and Gertrude Schottenfels, adapted the material for children. All based their work on nineteenth-century German publications, and each took a different approach to the violence of the female protagonist, Kriemhild. These range from the exculpatory – a rewriting which eliminates female-authored violence; a legalistic defence of insanity; a subtle shifting of the blame on to male characters – to a moralizing rejection which emphasizes Kriemhild's violence. The rationale for each approach is anchored in contemporary understandings of violent women.